Comparative Pathogenicity of Duck Hepatitis A Virus-1 Isolates in Experimentally Infected Pekin and Muscovy Ducklings - Hisham, Islam; Ellakany, Hany F.; Selim, Abdullah A.; Abdalla, Mohammed A. M.; Zain El-Abideen, Mohamed A.; Kilany, Walid H.; Ali, Ahmed; Elbestawy, Ahmed R. (Frontiers in Veterinary Science, 2020)
Duck hepatitis virus (DHV) has been always considered one of the threats endangering duck farming in Egypt since the 1960s. In the current study, suspected DHV samples (n=30) were obtained from commercial Pekin, Mulard (hybrid), and Muscovy duck farms and backyards in Beheira, Alexandria, Gharbia, Kafr El-Sheikh, and Giza provinces, between 2012 and 2017. Diseased 3-21 days-old ducklings showed a clinical history of high mortality rates and nervous signs. Samples were screened by RT-PCR targeting the 5’UTR region, and VP1 gene. The PCR confirmed samples (n=7) were isolated via allantoic route inoculation onto 9-day-old embryonated specific-pathogen-free chicken eggs. Embryos showed stunting, subcutaneous hemorrhages, and liver necrotic greenish-yellow foci. DHAV-1 isolates were genetically analyzed in comparison to other field and vaccine strains. Phylogenetic analyses of the full-length VP1 gene sequences revealed that the obtained DHAV-1 field isolates clustered into genetic group 4 alongside other Egyptian strains isolated during the same period (95.9%–99.72% similarity). Amino acid substitutions in the carboxyl-terminal of VP1 (I180T, G184E, D193N, and M213I) were identified in two strains. Also, deletion mutation at I189 was detected in three DHAV-1 strains. Additionally, the two amino acid residues E205 and N235 were common amongst the isolated strains and other virulent DHAV-1 strains. Two DHAV-1 isolates originated from Pekin source were selected for conducting the comparative pathogenicity testing based on detected point mutations at C-terminus of VP1. We evaluated the pathogenicity of these isolates by investigating clinical signs, mortality rates, gross pathological and microscopic lesions. The study revealed that experimentally infected Pekin and Muscovy ducklings showed similar clinical signs including squatting down, lateral recumbency, and spasmodic kicking. Muscovy showed milder pathological changes in the liver compared to Pekin ducklings. Histopathological findings supported the gross pathological lesions detected in both breeds. In conclusion, these data provide updated information on the genetic diversity and pathotyping of Egyptian DHAV-1 strains. To the best of our knowledge, this is the first report of comparative pathogenicity of recent DHAV-1 strains in Pekin and Muscovy ducklings in Egypt and the Middle East region.